Language Politeness of Presidential and Vice Presidential Candidates 2024-2029 Period in Campaign Impressions on TikTok Social Media - Ulfa, Ulfa; Syuroyah, Do'atusy; Jaja, Jaja; Rosmaya, Elin (Allure Journal, 2024)
To attract public attention, presidential and vice-presidential candidates conduct campaign activities as a form of introduction and delivery of their work programs through 'sweet message and promise'. In delivering these messages, intentionally or unintentionally, sometimes the candidates use language that is less polite. This is interesting to study from the aspect of politeness. Therefore, the researchers were interested in examining the language politeness This research was conducted using descriptive research approach. The theory used was Leech's politeness principle. The research data were in the form of expressions containing the maxims of politeness sourced from TikTok social media campaign showed and obtained using documentation techniques with the instrument of documentation study guidelines. Then, the data were processed using the extra lingual pairing method. From the results of the study, it is concluded that the maxim of generosity is the most widely used maxim in the campaign for the election of the president and vice president of Indonesia for the 2024 elections. Through the use of this maxim, candidates try to humble themselves in the hope of gaining public sympathy so as to get a lot of votes and win the contestation. The contemporary context, the specific application of politeness theory to political campaigns on a modern social media platform became the novelty of this study. By pursuing these avenues, future researchers can deepen the understanding of political communication strategies and their effects on the electorate.